The use of cryptotype in the comparison by Supranational Courts: brief remarks from the ECJ’s judgement on the early retirement age for Polish Supreme judges - Spadaro, Ignazio (Diritto Pubblico Europeo - Rassegna online, 2023)
In the case Commission v. Poland, C-619/18, delivered on 24th June 2019, the ECJ criticized Polish new Supreme Court Act (then repealed), by alleging that retroactive lowering of retirement age of the judges, and single discretionary extensions granted by the President of the Republic, could have jeopardized the independence of that body from the political power, in violation of Article 19(1) TEU. In the grounding, the European Judges recalled the rulings on the cases ASJP (C-64/16) and Fuchs and Köhler (C-159/10, C160/10), which they should have taken into account in terms of comparison. The paper starts from a short reconstruction of the ruling, then it determines if the distinguishing that it does between the Polish law and the national provisions of the cases mentioned above is fully embraceable. Finally, it stresses the key-role played by the political and ideological framework, as implicit but true term in the comparison made by the Court, and shows the possible impact on the guarantee function played by the ECJ